Evaluation of nitrogen and phosphorus in surface reservoirs of the semi-arid region of Brazil using mass balance - Fernandes Praxedes, Carine; Bezerra Lopes, Fernando; Maia de Andrade, Eunice; Teixeira da Silva, Thiago; Becker, Helena (Revista Ciência Agronômica, 2023)
Water reservoirs were built in the semi-arid region to mitigate the eff ects of drought and water scarcity. However, thesereservoirs are subject to variables that impact the volume and quality of the stored water, with the contribution of such nutrients as TotalNitrogen (TN) and Total Phosphorus (TP) being one of the main factors in intensifying the eutrophication process. The aim of this studywas to quantify the principal inputs and outputs of nutrients (N and P) and calculate the nutrient balance, in order to verify the infl uenceof seasonality on the import and export of these nutrients in surface reservoirs of the semi-arid region of Brazil. Seven campaigns werecarried out between 2015 and 2016, with water samples collected at fi ve points in the Pereira de Miranda reservoir and four in theGeneral Sampaio reservoir. The infl ow of nutrients was greater when the infl ow rate of the water was higher. The balance showed theaccumulation of 22.8 tons of TN and 2.8 tons of TP in the Pereira de Miranda reservoir, and 13 tons of TN and 1.5 tons of TP in theGeneral Sampaio. These reservoirs are therefore retaining nutrients, acting as a storage site for nutrients transported by surface runoff inthe basin of the Curu River. This increase in storage occurred mainly during the rainy season, when nutrient retention by the reservoirsimpaired water quality, resulting in eutrophication, and making it diffi cult to meet the uses for which the reservoirs were intended.